2022
DOI: 10.1177/02557614221074378
|View full text |Cite
|
Sign up to set email alerts
|

Learner-centered pedagogy and student engagement in a virtual elementary instrumental music program

Abstract: The purpose of this qualitative case study was to examine the effect of learner-centered pedagogy on student engagement in a virtual elementary instrumental music program. Eleven fourth- and fifth-grade students from an elementary school in the Southeastern United States worked remotely toward creating a virtual performance over 28 weeks. All songs were chosen by students, and they were given the liberty to choose which parts to practice. Data were collected through regular Flipgrid practice videos, bi-weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Meanwhile, the Netherlands has implemented a student-centered curriculum up to the undergraduate education stage (Waterval et al, 2017) so that students are allowed to take courses according to their needs. In the United States, a student-centered curriculum is given from the moment the child enters elementary school (Beirnes, 2022) so teachers can identify students' talents and interests from the start.…”
Section: Independent Curriculum In Indonesiamentioning
confidence: 99%
“…Meanwhile, the Netherlands has implemented a student-centered curriculum up to the undergraduate education stage (Waterval et al, 2017) so that students are allowed to take courses according to their needs. In the United States, a student-centered curriculum is given from the moment the child enters elementary school (Beirnes, 2022) so teachers can identify students' talents and interests from the start.…”
Section: Independent Curriculum In Indonesiamentioning
confidence: 99%
“…Martin et al argued that musical scores convey a wide range of information, describing the significance of the construction of musical scores, and arguing that performers can know how to sing through the scores, demonstrating that music conforms to the same language as the communicative role of text [12]. Beirnes, S explored the impact of a centered pedagogy on student engagement in vocal learning, arguing that participatory vocal teaching can greatly motivate students' interest in vocal practice and increase classroom engagement through students' self-efficacy [13]. Jason, M et al explored the impact of audio recording and playback on students' self-assessment of vocal learning.…”
Section: Introductionmentioning
confidence: 99%
“…The performance test indicates that this system has an error rate of around 0.01% when integrating teaching resources. Literature [14] investigated the impact of a virtual basic instrumental music course on students' music learning by collecting regular Flipgrid practice videos and journal data through virtual performance experiments, and the results of the study showed that the incorporation of a virtual instrumental music course in music majors improves students' self-efficacy and motivation for independent learning of music.…”
Section: Introductionmentioning
confidence: 99%